An H i absorption distance to the black hole candidate X-ray binary MAXI J1535-571 - Chauhan, Jaiverdhan; Miller-Jones, James; Anderson, Gemma; Raja, W.; Bahramian, Arash; Hotan, A.; Indermuehle, B.; Whiting, M.; Allison, J.R.; Anderson, C.; Bunton, J.; Koribalski, B.; et al. (OXFORD UNIV PRESS, 2019)
With the Australian Square Kilometre Array Pathfinder (ASKAP) we monitored the black hole candidate X-ray binary MAXI J1535-571 over seven epochs from 2017 September 21 to October 2. Using ASKAP observations, we studied the H i absorption spectrum from gas clouds along the line of sight and thereby constrained the distance to the source. The maximum negative radial velocities measured from the H i absorption spectra for MAXI J1535-571 and an extragalactic source in the same field of view are -69 ± 4 and -89 ± 4 km s-1, respectively. This rules out the far kinematic distance (9.3+0.5 -0.6 kpc), giving a most likely distance of 4.1+0.6 -0.5 kpc, with a strong upper limit of the tangent point at 6.7+0.1 -0.2 kpc. At our preferred distance, the peak unabsorbed luminosity of MAXI J1535-571 was >78 per cent of the Eddington luminosity, and shows that the soft-to-hard spectral state transition occurred at the very low luminosity of (1.2-3.4) × 10-5 times the Eddington luminosity. Finally, this study highlights the capabilities of new wide-field radio telescopes to probe Galactic transient outbursts, by allowing us to observe both a target source and a background comparison source in a single telescope pointing.